The normative property dualism argument - Hambly, Jesse (The philosophical quarterly, 2025)
In this paper, I develop an argument against a type of Non-Analytic Normative Naturalism. This argument, the Normative Property Dualism Argument, suggests that if Non-Analytic Normative Naturalists posit that normative properties are identical to natural properties and that such identities are a posteriori, they will be forced to posit that these properties that are both normative and natural have higher-order normative properties of their own.